The Effect of Work Motivation and Work Skill on Career Decision Moderated by Internship Program in The Hotel Industry of Lampung Province - M. Sholahudin; Ayi Ahadiat; Ribhan (PT. Hasba Edukasi Mandiri, 2025)
The global tourism and hospitality industry continues to show rapid growth, making significant contributions to economic development, job creation, and education. Lampung Province is experiencing similar developments, marked by an increase in the number of tourits visits and significant growth in accommodation businesses. This competitive hospitality sector demands human resources (HR) with superior skills (work skills) and work motivation, which can be obtained through internship programs. Internship programs are designed to provide practical experience to students, so that they are better prepared to face the world of work. This study aims to analyze the influence of work motivation and work skills on career decisions, with internship programs as a moderating variable in the Lampung Province hospitality industry. The study focuses on hotel employees from formal and non-formal educational institutions, who have participated in internship programs in accordance with vocational education policies in Indonesia. With this approach, the study is expected to fill the gap from previous studies, as well as provide recommendations for educational institution managers and industry players to improve the work readiness of graduates in supporting the competitiveness of the hospitality sector. This research methodology uses a quantitative approach to test the relationship between variables. The object of this study was starred hotel workers in Lampung who participated in an internship program, with a population of 1,499 people. A sample of 266 respondents was selected using purposive sampling based on internship experience criteria, according to Roscoe's theory for multivariate research. The test results showed that Work Motivation and Work Skill had a positive and significant effect on Career Decision. Internship Program moderation also strengthened the relationship, where Work Motivation and Work Skill moderated by the Internship Program significantly influenced Career Decision. This confirms the importance of motivation, skills, and internship experience in supporting career decisions.